Cross-Sectional Correlation Robust Tests for Panel Cointegration - Christoph Hanck (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
We use meta analytic combination procedures to develop new tests for panel cointegration. The main idea consists in combining p-values from time series cointegration tests on the different units of the panel. The tests are robust to heterogeneity as well as to cross-sectional dependence between the different units of the panel. To achieve the latter, we employ a sieve bootstrap procedure with joint resampling of the residuals of the different units. A simulation study shows that the suggested bootstrap tests can have substantially smaller error-in-rejection probabilities than tests ignoring the presence of cross-sectional dependence while preserving high power. We apply the tests to a panel of Post-Bretton Woods data to test for weak Purchasing Power Parity (PPP).
Keywords: 519; panel cointegration tests; cross-sectional dependence; sieve bootstrap